Extensive study of the private property market in Singapore - Lim, Sok Ngin (2008)
We take a look at the factors that can best explain the trend in the property price indices (PPIs) of the five different types of private residential property over a period of 16 years – from the first quarter of 1982 to the second quarter of 1998. We also establish that the behaviour of private property prices for the period 1980s differed from that for the period 1990s and investigate which of the parameters of the private housing price function have changed for each housing type.